2022
DOI: 10.1186/s12916-021-02229-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of diet in renal cell carcinoma incidence: an umbrella review of meta-analyses of observational studies

Abstract: Background Evidence associating diet with the incidence of renal cell carcinoma (RCC) is inconclusive. We aimed to summarize evidence associating dietary factors with RCC incidence and assess the strength and validity of this evidence. Methods We conducted an umbrella review of systematic reviews or meta-analyses (SRoMAs) that assessed the association between diet and RCC incidence. Through April 2021, PubMed, Web of Science, Embase, The Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 175 publications
(187 reference statements)
0
6
0
Order By: Relevance
“…Observational studies suggest that cruciferous vegetables intake is associated with a lower risk of renal cancer. [ 15 , 16 , 17 ] In this context, the impact of the poorly explored ITC erucin on renal cancer was studied. For this purpose, we selected 786‐O cells, a well‐known ccRCC model, and Vero‐E6 cells as a non‐tumor control model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies suggest that cruciferous vegetables intake is associated with a lower risk of renal cancer. [ 15 , 16 , 17 ] In this context, the impact of the poorly explored ITC erucin on renal cancer was studied. For this purpose, we selected 786‐O cells, a well‐known ccRCC model, and Vero‐E6 cells as a non‐tumor control model.…”
Section: Resultsmentioning
confidence: 99%
“…This topic becomes even more relevant since meta‐analyses of observational studies suggested that the cruciferous vegetables intake is associated with a lower risk of renal cancer. [ 15 , 16 , 17 ] In this context, the present study aims at exploring the effects of erucin in kidney cancer cell biology. Endpoints relevant to cancer progression were evaluated and the molecular mechanisms underlying the observed phenotypes were explored.…”
Section: Introductionmentioning
confidence: 99%
“…As described in previous umbrella reviews, p < 0.1 was considered to indicate statistically significant differences. 22,25 In addition, we conducted sensitivity analysis for the meta-analysis with class I-III, excluding original studies with a total sample size of <100. The results and the level of evidence were re-analyzed to test the robustness of the results and reduce bias caused by the small sample study.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether too many studies had formal statistically significant results, we carried out the excess significance bias (ESB) test. As described in previous umbrella reviews, p < 0.1 was considered to indicate statistically significant differences 22,25 . In addition, we conducted sensitivity analysis for the meta‐analysis with class I–III, excluding original studies with a total sample size of <100.…”
Section: Methodsmentioning
confidence: 99%
“…High-fat diets have been linked to the exacerbation of ccRCC onset and progression in prior epidemiological research [ 29 ], as these diets provide a rich supply of substrates for adipocytes that can enable the synthesis of LDs and contribute to the incidence of obesity, which necessitates lipid reduction. Tumor cells with dysregulated lipid metabolism must similarly reduce lipid levels through the regulated accumulation of LDs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%